1999
DOI: 10.1001/archopht.117.7.880
|View full text |Cite
|
Sign up to set email alerts
|

Optic Nerve Hypoplasia With Isolated Tortuosity of the Retinal Veins

Abstract: To investigate whether children with optic nerve hypoplasia and pituitary hormone insufficiencies have specific ocular fundus characteristics that may facilitate early diagnosis and treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
2
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 30 publications
3
13
2
1
Order By: Relevance
“…50,51 In the present study, we report a clear association between vascular tortuosity and retinal dyfunction, as indicated by absent pattern ERGs. This supports a link between vascular morphology and retinal dysfunction in a subset of our cases.…”
Section: Discussionsupporting
confidence: 61%
“…50,51 In the present study, we report a clear association between vascular tortuosity and retinal dyfunction, as indicated by absent pattern ERGs. This supports a link between vascular morphology and retinal dysfunction in a subset of our cases.…”
Section: Discussionsupporting
confidence: 61%
“…69 ONH may be associated with tortuosity of the retinal vasculature. 70 This feature has in one study also been shown to be associated with the development of endocrinopathy. 70 A persistent grey appearance has also been described.…”
Section: Clinical Featuresmentioning
confidence: 87%
“…70 This feature has in one study also been shown to be associated with the development of endocrinopathy. 70 A persistent grey appearance has also been described. 71 The ratio of the distance between the centre of the optic disc to the centre of the macula (DM) and the mean optic disc diameter (DD) (ie the DM to DD ratio) provides an index of the size of the optic disc on clinical examination and on photography 72,73 (Figure 4).…”
Section: Clinical Featuresmentioning
confidence: 87%
“…Bilateral or unilateral optic nerve hypoplasia is often associated with hypopituitarism [11] . When it is also associated with absence of the septum pellucidum, the condition is known as septo-optic dysplasia [19] . But macular ectopia associated with growth hormone deficiency has not been described.…”
Section: Discussionmentioning
confidence: 99%